2009
DOI: 10.1163/156856208x393518
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Enzymatically-Digested Hyaluronan by Liver Endothelial Cells in Vivo and in Vitro

Abstract: Intravenously-injected hyaluronan (HA) is distributed into liver in which endothelium is a site of uptake and degradation of HA. The role and fate of HA have been widely investigated; however, effects of size and dose of HA on its metabolism have not been well documented yet. To investigate these effects, we prepared fluorescein-labeled HAs, according to the modified methods described by de Belder and Wik, which were enzymatically digested. The 90 kDa fluorescein-labeled HA gradually accumulated in a liver tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…These results are also supported by the fact that liver endothelial cells could take up HA both in vitro and in vivo. 16) Therefore, HA clearly has the ability to target liver endothelial cells. We next hypothesized that free HA coated liposomes could be accumulated to a greater extent in liver endothelial cells than non-coated liposomes, because free HA could be introduced on the surface of liposomes via electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are also supported by the fact that liver endothelial cells could take up HA both in vitro and in vivo. 16) Therefore, HA clearly has the ability to target liver endothelial cells. We next hypothesized that free HA coated liposomes could be accumulated to a greater extent in liver endothelial cells than non-coated liposomes, because free HA could be introduced on the surface of liposomes via electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…16) Further studies are clearly needed for the more selective delivery to liver endothelial cells to be achieved by escaping uptake by kupffer cells. Optimization of the molecular weight of HA, and the use of a pH sensitive cationic lipid are some promising candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein was covalently attached to 1.2 MDa HA according to the published procedure (Mochizuki et al, 2009), resulting in a fluorescein/HA disaccharide ratio of~0.02-0.03 as reported by the authors. Two different batches of flHA were used throughout this study.…”
Section: Flha Labeling and Functional Characterizationmentioning
confidence: 99%
“…The same authors also reported that the total amount of excretion into bile within 24 hours was reported to be very low, 0.7% of the administered dose, and the total amount of excretion HA into feces, within 100 hours of administration, was also very small, about 0.5% of the administered dose (25) (25). Research on the effects of size and dose of fluorescein-labeled HA on its metabolism has shown that 60% of the tail vein injected 90 kDa HA accumulated in the liver , while both the 3 kDa and 10 kDa fluorescein-labeled HA were quickly excreted in urine with no accumulation in any tissues (31). As such, neither HA nor any other gadolinium based MRI agents administered intravenously are known to have any significant gastrointestinal uptake.…”
Section: Discussionmentioning
confidence: 99%